Recovery of atrophic parotid glands in rats fed a liquid diet by switching to a pellet diet. (December 2018) - Takahashi, Shigeru; Takebuchi, Rui; Taniwaki, Hiroto; Domon, Takanori
Highlights: The parotid glands, made atrophic by a liquid diet, recovered in the weight after changing the diet from liquid to pellet form. The atrophic acinar cells recovered in size after the diet change. Acinar cells actively proliferated and apoptosis in acinar cells diminished to the normal level after the diet change. The findings in the present study show that by changing the liquid diet to pellet diet increased which both the size and number of acinar cells contributed to the recovery of the parotid glands. Abstract: Objective: In this study, we aimed to clarify how parotid glands, made atrophic by a liquid diet, recover after diet change. Design: Seven-week-old male Wistar rats were fed a pellet (control group) or a liquid diet (experimental group) for the first 14 days. Thereafter, all animals were fed a pellet diet for up to 14 days (days 0–14). The parotid glands were removed, weighed and examined histologically and ultrastructurally. Immunohistochemistry was performed for BrdU, a marker of proliferating cells, and Casp-3, a marker of apoptotic cells. Results: Feeding of a liquid diet for 14 days induced atrophy of the parotid glands. Histologically, acinar cells were small on day 0, compared with the control group. After changing the diet from liquid to pellet form, acinar cells increased in size over time, recovering nearly fully by day 7. Many BrdU-positive acinar cells were observed in the glands in the experimental group on days 1 and 3. Although more acinar cells were Casp-3-positive compared with the control group on day 0, there was no difference between the two groups after the diet change. Ultrastructurally, the cellular organelles did not exhibit a substantial alteration, except for an increase in secretory granules following diet change. Conclusions: Our findings suggest that atrophic parotid glands are able to recover to their normal size by switching the diet from liquid to pellet form and that an increase in both the size and number of acinar cells plays an important role in this recovery process.